2017
DOI: 10.1007/s00421-017-3737-3
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary activation and variability during maximal dynamic contractions with aging

Abstract: Whether reduced supraspinal activation contributes to age-related reductions in maximal torque during dynamic contractions is not known. The purpose was to determine whether there are age differences in voluntary activation and its variability when assessed with stimulation at the motor cortex and the muscle during maximal isometric, concentric and eccentric contractions. Thirty young (23.6±4.1 years) and 31 old (69.0±5.2 years) adults performed maximal isometric, shortening (concentric) and lengthening (eccen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 80 publications
(138 reference statements)
1
15
0
Order By: Relevance
“…An important finding of the current investigation is the existence of a central origin of the force modulation in patients with PD. For maximal isometric contractions in healthy old population, increased variability of activation could suggest marked neural or supraspinal deficits, which are a precursor in limiting capacity and activation with advanced aging 46 . Regarding the pathology of PD, basal ganglia dysfunction may interfere with efficient cortical motor activation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…An important finding of the current investigation is the existence of a central origin of the force modulation in patients with PD. For maximal isometric contractions in healthy old population, increased variability of activation could suggest marked neural or supraspinal deficits, which are a precursor in limiting capacity and activation with advanced aging 46 . Regarding the pathology of PD, basal ganglia dysfunction may interfere with efficient cortical motor activation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…2016; Rozand et al . 2017). Similarly, we found no age differences in any contractile properties of the isolated fibres, other than a lower absolute P o and power output in MHC II fibres from old compared to young adults (Figs and ).…”
Section: Discussionmentioning
confidence: 99%
“…1; Aruin et al 1996) as well as during adjustments to perturbations, both anticipatory (Aruin and Almeida 1997) and corrective (Latash et al 1993). A number of studies reported increased levels of coactivation during movements performed by healthy older adults (Lee et al 2015;Nagai et al 2011;Rozand et al 2017). Patients with a variety of neurological disorders show increased levels of muscle coactivation.…”
Section: Coactivation Patterns Across Populationsmentioning
confidence: 99%